Challenges of glycosylation analysis and control: an integrated approach to producing optimal and consistent therapeutic drugs. Issue 5 (May 2016) - Zhang, Peiqing; Woen, Susanto; Wang, Tianhua; Liau, Brian; Zhao, Sophie; Chen, Chen; Yang, Yuansheng; Song, Zhiwei; Wormald, Mark R.; Yu, Chuanfei; Rudd, Pauline M.
Highlights: Glycosylation of antibodies has a range of effects on their binding and effector functions. Regulatory agencies require stringent glycan analysis to ensure safety and efficacy. Many tools are available to address different questions in glycan analysis. Glycosylation is influenced by the host cell line, the cell culture and purification processes. Controlling glycosylation requires a systems biology understanding and integrated approach. Abstract : Glycosylation of therapeutic proteins has a profound impact on their safety and efficacy. Many factors shape the glycosylation of biotherapeutics, ranging from expression systems and cell culture processes to downstream purification strategies. Various analytical technologies have been developed to address questions concerning different aspects of glycosylation. Informatics tools are also crucial for a systematic understanding of the glycosylation processes. Hence, an integrated approach is required to harness glycosylation for the production of optimal and consistent glycoprotein-based therapeutic drugs. Here, we review the latest developments and challenges in glycosylation analysis and control in the context of bioprocessing monoclonal antibodies. Teaser: This review provides an integrated roadmap for evaluating the impact of glycosylation in the development and production of biopharmaceuticals, and the associated challenges in glycosylation analysis and process control.